PEMANFAATAN KOMPOS AMPAS SAGU DAN PUPUK FOSFOR UNTUK PERTUMBUHAN DAN PRODUKSI TANAMAN OKRA (Abelmoschus esculentus (L.) Moench) - Desi Ratna Sari; Nurbaiti; Idwar (DINAMIKA PERTANIAN, 2021)
The purpose of this study is to determine the effect of the interaction of sago pulp compost and phosphorus fertilizer, the single factor of sago pulp compost and phosphorus fertilizer, and to obtain the optimal dosage of sago pulp compost and phosphorus fertilizer for growth and production of okra plants. The study was conducted at the Experimental farm of the Faculty of Agriculture, University of Riau. The study used a factorial randomized block design (RCBD). The first factor is the dosage of sago pulp compost (K) K0 : 0 kg per plot (0 tons.ha-1), K1 : 1,75 kg per plot (8,75 tons.ha-1), K2 : 3,50 kg per plot (17,50 tons.ha-1) and K3 : 5,25 kg per plot (26,25 tons.ha-1). The second factor is the dosage of SP-36 phosphorus fertilizer (P) P0 : 0 g SP-36 per plot (0 kg.ha-1), P1 : 10 g SP-36 per plot (50 kg.ha-1) and P2 : 20 g SP-36 per plot (100 kg.ha-1). The parameters observed were plant height, number of fruits per plant, fruit length, fruit diameter, fruit weight per plant, number of fruits per plot, and fruit weight per plot. The data obtained were statistically analyzed using variance and continued with Duncan's New Multiple Range Test at the level 5%. The results showed that the interaction of sago pulp compost and phosphorus fertilizer could increase plant height, fruit length, fruit diameter, fruit weight per plant, number of fruits per plot, and fruit weight per plot. The best dosage of the growth and production of okra plants is 5,25 kg of sago pulp compost per plot and 20 g SP-36 of phosphorus fertilizer per plot, but the replicated 5,25 kg of sago pulp compost per plot and 10 g SP-36 of phosphorus fertilizer per plot was the optimal dosage that able to produce okra as much 7,01 tons.ha-1.